Treatment of MTBE Contaminated Water by Means of Granular Activated Carbon (GAC) Adsorption - Nader Mokhtarani; Elham Shafiee (مهندسی منابع آب, 2020)
Nowadays, Producing and using chemical compounds in different industrials has caused environmental pollution. One of these compounds that can bring a widespread pollution in natural resources is Methyl Tert-Butyl Ether (MTBE). This organic compound that is produced in petrochemical industries is used as a substitute to produce lead free gasoline in all over the world. Human exposure to MTBE may cause dizziness, coughing, fever, headaches, vomiting, muscular aches, sleepiness and skin and eye irritation. Concerning the destructive consequences of MTBE on the environment, and human health, clearing polluted resources are vital. The main objective of this study is dedicated to treat MTBE-contaminated waters through adsorption process in the presence of granular activated carbon (GAC). In this study, the effect of pH as well as exposure time on the removal of MTBE from aqueous solution have been examined and finally the efficacies of the process is assessed in terms of organic compounds removal and GAC reusability. According to the results, the adsorption capacity of used activated carbon depends considerably on the PH and reaction time. In this study, after 45 minutes of reaction time at PH of 8 the maximum COD removal efficiency of 62% was achieved. In this research both the Langmuir and Freundlich isotherm model best represented the MTBE adsorption behavior of GAC, having R2 of 92.2% and 84.6%, respectively. Moreover, maximum capacity of adsorption, in optimized condition, was estimated to be 67 mg of COD per each gr of GAC.